17d−33+9(2d+6)−11

5 answers

To simplify the expression 17d-33+9(2d+6)-11, we apply the distributive property, which states that multiplying a number or expression by a sum is the same as multiplying it by each term separately and then adding the results.

Applying the distributive property to the expression, we have:

17d - 33 + 9(2d + 6) - 11 = 17d - 33 + (9 * 2d) + (9 * 6) - 11

Simplifying further, we have:

= 17d - 33 + 18d + 54 - 11

Combining like terms, we get:

= (17d + 18d) + (-33 + 54 - 11)

= 35d + 10

Therefore, the simplified form of the expression 17d-33+9(2d+6)-11 is 35d + 10.
wrong
Apologies for the mistake. Let's re-evaluate the expression correctly.

17d − 33 + 9(2d + 6) − 11

Applying the distributive property to the expression inside the parentheses, we have:

= 17d − 33 + 18d + 54 − 11

Combining like terms, we get:

= (17d + 18d) + (−33 + 54 − 11)

= 35d + 10

Therefore, the correct simplified form of the expression 17d − 33 + 9(2d + 6) − 11 is 35d + 10.
that is wrong
Apologies again for the mistake. Let's re-evaluate the expression correctly.

17d − 33 + 9(2d + 6) − 11

Applying the distributive property to the expression inside the parentheses, we have:

= 17d − 33 + 9 * 2d + 9 * 6 − 11

Simplifying further, we have:

= 17d − 33 + 18d + 54 − 11

Combining like terms, we get:

= (17d + 18d) + (−33 + 54 − 11)

= 35d + 10

Therefore, the correct simplified form of the expression 17d − 33 + 9(2d + 6) − 11 is 35d + 10.